TBLT -Based Active Speaking Textbook Design to Improve Speaking Ability of PAI Students - Agus Salim Marpaung Salim; Putri Suaidah Pulungan; Yuliana Dewi; Nurhikmah Pohan (CV. Edujavare Publishing, 2026)
This study aims to design an Active Speaking textbook based on Task-Based Language Teaching (TBLT) to enhance the speaking skills of Islamic Education (PAI) students at IAIDU Asahan. The TBLT approach promotes the use of authentic and meaningful tasks that reflect real-life communication, encouraging active participation, collaboration, and practical language use. However, the limited availability of contextual learning materials and the continued reliance on conventional teaching methods have hindered the development of students' speaking competence. To address these challenges, the textbook was developed using the ADDIE instructional design model , which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved identifying students' learning needs, designing the instructional materials, and evaluating the effectiveness of the textbook in improving English-speaking proficiency. The findings are expected to demonstrate that the TBLT-based Active Speaking textbook effectively enhances students' speaking skills by providing authentic communicative tasks and interactive learning experiences. Furthermore, the developed textbook contributes to the advancement of innovative, relevant, and practice-oriented English language instruction, enabling students to communicate, interact, and collaborate effectively in both academic and global contexts. Keywords: Active Speaking Textbook Design, TBLT, ADDIE Model, Speaking Skills, Islamic Education Students, IAIDU Asahan.